Cervicovaginal Microbiomes–Threats and Possibilities. (July 2016) - Reid, Gregor
Abstract : The microbiome of the vagina has universal traits that override race, diet, lifestyle, and socioeconomic status. While five community state types have been proposed, the actual number is likely closer to ten. Nevertheless, while lactobacilli dominate in health for most women, a highly diverse community or single pathogens are associated with morbidity. The fact that four or five Lactobacillus species are dominant in healthy women worldwide, raises questions of why they evolved in this niche, what they are doing, and how their apparent protective properties can be harnessed? This opinion article explores this universality, elements of lactobacilli that may imprint women's health and that of their offspring, and proposes key areas for future study. Trends: The female reproductive tract is vital to human survival. Healthy homeostasis is maintained in large part by Lactobacillus bacteria, irrespective of where a woman lives, her diet, lifestyle, or sexual activity. Dysbiosis leads to morbidity and adverse quality of life, yet methods of detection and management are poor and have not been improved for over 30 years. The ability to manipulate 'beneficial' microbes, including administering probiotic lactobacilli, forms a valid alternative intervention worthy of further consideration.